Penerapan Terapi Perilaku Spesialis Keperawatan Jiwa Pada Klien Dengan Risiko Perilaku Kekerasan Menggunakan Pendekatan Teori Johnson Dan Teori Lewin - Fajar Rinawati (coba, 2015)
Clients with mental disorder usually admited to the hospital because of their maladaptive behavior, such as hurting themselves, other people or destroying environment. This condition need immediate treatment by controling client’disruptive behaviors. Behavior therapy is a therapy used to modify maladaptive behavior becomes adaptive. The purpose of this study was to determine the application of behavior therapy for violent risked behavior clients in Acute Ward. The analysis of this paper consisted of 10 clients with violent risked behavior who were the subjects of behavior therapy. The results showed that there were alteration of signs and symptoms, and ability of clients. Behavior therapy can be used not only for clients with self care deficit but also for clients with violent risked behavior. Behavior therapy appropriately used for acute inpatients with maladaptive behavior.